Clinical research on minimally invasive internal fixation for the treatment of anterior ring injury in tile C pelvic fracture. Issue 30 (24th July 2020) - Sun, Xiaochen; Yan, Huimin; Wang, Jianmin; Liu, Zhaojie; Tian, Wei; Jia, Jian
Abstract : Abstract: The aim of this study is to explore the clinical outcome and indications in treating anterior ring injury of Tile C pelvic fracture with minimally invasive internal fixation. We retrospectively reviewed 18 patients (aged 25–62, 34.2 ± 7.4) with 26 pelvic anterior ring injuries of Tile C pelvic fracture treated with minimally invasive internal fixation in our hospital were from January 2012 to August 2016. Two cases were pubic symphysis diastasis, 15 were anterior ring fracture (7 were bilateral), and 1 was vertical displacement of pubic symphysis associated with pubic ramus fracture. According to Tile classification, 8, 4, and 6 cases were types C1, C2, and C3, respectively. All patients accepted the operation of pelvic fractures on both rings, while the anterior ring injuries were treated with minimally invasive internal fixation. The period from injury to operation was 5 to 32 days (11.2 ± 3.7). Four patients had pubic symphysis diastasis or pelvic anterior ring fracture medial obturator foramen reduced with modified Pfannenstiel incision and fixed with cannulated screws, 14 patients (22 fractures) had a fractured lateral obturator foramen reduced with modified Pfannenstiel incision associated with small iliac crest incision and fixed with locking reconstruction plates. Clinical data, such as operation time, intraoperative bleeding, Matta standard to assess the reduction quality of fracture, and complications, were collected and analyzed. The operation time ranged from 30 to 65 minutes (42.8 ± 18.7), and the intraoperative bleeding volume was 30 to 150 mL (66.5 ± 22.8). All cases were continuously followed-up for 16 to 42 months (30.2 ± 4.6). All fractures were healed between 3 and 9 months postoperatively (4.9 ± 2.7 months). According to the Matta standard assessment, 18, 7, and 1 cases were excellent, good, and fair, respectively, with a 96.2% (25/26) rate of satisfaction. Neither reduction loss, fixation failure, nor infection occurred; complications included 1 patient with fatal liquefaction, 1 patient had lateral femoral cutaneous nerve injury, and 1 patient complained of discomfort in the inguinal area due to fixation stimulation. Minimally invasive internal fixation for pelvic anterior ring injury in Tile C pelvic fracture has the advantages of less damage, safer manipulation, less complications, and good prognosis.